2018
DOI: 10.3390/en11071705
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Power-Split HEVs Based on Total Cost of Ownership and CO2 Emission Minimization

Abstract: An optimal design toolbox for hybrid electric vehicles has been developed and applied to three different vehicle segments (a compact vehicle, a small SUV and a medium-size SUV) for two separate power-split hybrid layouts, both equipped with a diesel engine. One layout features a (3gTR) whereas the other lacks of the additional 3-gear transmission. The toolbox combines the optimization of the vehicle design to that of the control strategy and is based on the minimization of the total cost of ownership (TCO) ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The need to comply with the more and more stringent regulations in terms of CO 2 and pollutant emissions is pushing the automotive industry to develop innovative technologies. Recent trends which may produce the highest benefits include engine downsizing [1], alternative fuels (such as Compressed Natural Gas (CNG) and biofuels) [2], innovative combustion concepts such as Homogeneous Charge Compression Ignition (HCCI) and Premixed Charge Compression Ignition (PCCI) [3], advanced high-pressure common rail systems [4,5], innovative combustion controls [6][7][8], innovative after-treatment system (ATS) technologies [9], kinetic and thermal energy recovery [10], vehicle road load reduction [11], powertrain electrification [12], and vehicle connectivity (V2X technologies) [13]. In particular, in ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to comply with the more and more stringent regulations in terms of CO 2 and pollutant emissions is pushing the automotive industry to develop innovative technologies. Recent trends which may produce the highest benefits include engine downsizing [1], alternative fuels (such as Compressed Natural Gas (CNG) and biofuels) [2], innovative combustion concepts such as Homogeneous Charge Compression Ignition (HCCI) and Premixed Charge Compression Ignition (PCCI) [3], advanced high-pressure common rail systems [4,5], innovative combustion controls [6][7][8], innovative after-treatment system (ATS) technologies [9], kinetic and thermal energy recovery [10], vehicle road load reduction [11], powertrain electrification [12], and vehicle connectivity (V2X technologies) [13]. In particular, in ref.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported in ref. [12] presents a tool for the optimal design of hybrid vehicles equipped with diesel engines, and the consequent benefits in terms of costs and CO 2 emission reduction. Finally, in ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the technical literature, different hybrid topologies and many Energy Management Systems (EMS) were proposed [1,2] nevertheless hybrid architectures can be mainly divided in two categories: parallel and series hybrid vehicles. Regarding parallel architecture, this structure is mainly used on medium size cars and can be realized either with one electrical machine [3][4][5][6][7], two electrical machines and a planetary gearbox (also known as power split or series/parallel hybrid) [8][9][10][11][12][13][14] can be realized with a compound structured permanent-magnet motor [15]. As far as series architecture is concerned, this topology was mainly designed, until now, for urban bus applications [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent technologies have been developed to reduce fuel consumption and include engine downsizing [1], alternative fuels [2], innovative combustion concepts [3,4], advanced high-pressure injection systems [5][6][7][8][9][10], model-based control [11][12][13][14][15], advanced aftertreatment systems [16], kinetic and thermal energy recovery [17], vehicle lightweight [18], electrification of the powertrain [19], and vehicle connectivity [20].…”
Section: Introductionmentioning
confidence: 99%
“…The IMPERIUM consortium includes several partners from the academia and industry (see [13][14][15][16][17][18][19][20][21][22]). At the end of the project, three heavy-duty demonstrators were realized, in order to show the benefits achieved by means of the developed technologies.…”
Section: Introductionmentioning
confidence: 99%